Quality of life of patients affected by cerebral vascular accident - Silva, Francisco Valter Miranda; Ana Beatriz Castro Oliveira; Claudiana Batista de Brito; Franklin Douglas Saboia de Sousa; Elizandra Menezes Maia; João Victor Pereira da Silva; Wênia Sâmia Bandeira Ferreira; Paula Pessoa de Brito Nunes (Journal of Health Care, 2021)
Stroke is a serious disease, its sequelae can compromise the quality of life of the people affected. Objective: To analyze the quality of life of stroke patients. Methodology: This is a descriptive, exploratory cross-sectional study, with a sample composed of stroke patients of both sexes, aged over 21 years. The questionnaires were applied: Mini-Mental State Examination (MMSE), Sociodemographic and the Medical Outcomes Short-Form 36-item Health Survey (SF-36). Results: 20 patients were in attendance, only 15 of them reached the required MMSE to enter the research. 9 (60.0%) were male and 6 (40.0%) were female, aged over 60 years, aged from 60 to 69 years 6 (40.0%) and 71 to 79 years 2 (13.3%), in relation to race, white and brown were equal to 7 (46.7%), for the type of stroke it was observed that 11 (73.3%) of the patients suffered a stroke Ischemic and 4 (26.7%) Hemorrhagic Stroke. About the time of the stroke, 12 (80%) had had it for more than 1 year. Low scores were observed in all domains of the SF-36, mainly in the natural aspects (26.66), functional capacity (43.33), and emotional aspects (41.93). Conclusion: It was observed a compromise in the perception of Quality of Life (QOL) with low values in all domains, mainly in the physical, emotional and functional capacity, with a higher frequency in patients with a clinical diagnosis of ischemic stroke, aged over 60 years of male gender